Increased Mesostriatal Intrinsic Connectivity Associated With Cue Exposure in Adult Cannabis Users: Preliminary Findings - Kleinhans, Natalia M.; Terry, Garth E.; Kang, Dahyeon; Larsen, Sarah F.; Larimer, Mary E. (Addiction biology, 2025)
ABSTRACT Cue‐induced craving—the desire to use a drug triggered by exposure to cues associated with prior use—is a central mechanism in the development and maintenance of problematic substance use behaviours. Drug cues have the power to induce craving even in long‐term abstinent individuals, which has led clinicians to advise patients to avoid the people, places and objects that are associated with their use. This preliminary study builds on prior behavioural research that demonstrates that exposure to multimodal drug cues can increase craving even after the drug cues are removed from the environment. We used a novel fMRI paradigm that combined multimodal cannabis cue‐exposure with resting‐state functional connectivity to examine positive and negative functional connectivity (i.e., correlations and anticorrelations) between the ventral tegmental area (VTA) and the striatum, a circuit critically involved in reward processing and addiction. Intrinsic VTA‐striatal connectivity was measured in 28 individuals who use cannabis regularly (CU group) and 26 age‐ and sex‐matched controls who had never used cannabis before and after multimodal (visual and olfactory) cannabis cue exposure. Craving was assessed at baseline using the Marijuana Craving Questionnaire‐Short Form to test whether VTA‐striatal connectivity was correlated with self‐reported craving measured prior to the fMRI scan. There were no significant group differences in VTA‐striatal connectivity during the baseline resting‐state scan. However, following cue exposure, CU participants showed significantly greater VTA‐caudate connectivity compared to controls. Further, within the CU group, baseline craving was positively correlated with VTA‐striatal connectivity at both time points. Our preliminary findings support prior investigations demonstrating that alterations of mesostriatal connectivity are associated with cannabis use and craving in individuals with problematic cannabis use. In addition, the observation of altered connectivity during the post‐cue resting‐state scan—after multimodal cannabis cues were removed—suggests a potential neural mechanism by which cue exposure may contribute to relapse vulnerability in individuals with problematic cannabis use. We observed that resting‐state connectivity between the ventral tegmental area (VTA) and the nucleus accumbens and head of the caudate are anticorrelated. Preliminary findings show that cannabis cue‐exposure is associated with altered intrinsic connectivity between the VTA and the head of the caudate in the cannabis group after cannabis cues are no longer present. Further, within the cannabis group, craving measured prior to scanning was positively correlated with VTA‐striatal connectivity at both time points, independent of cannabis cue‐exposure.